COGNITIVE STRUCTURE STRENGTHENING STUDENTS OF SMK N 1 ARSE CLASS XII WITH LEARNING MODEL ADVANCE ORGANIZER BY GRANT STRUCTURED LKS BASED APOS THEORY - Abdul Rahman Hakim; Mara Bangun Harahap (Universitas Negeri Medan, 2013)
The purpose of this research: (1) Improving Students' Cognitive Structures through the Advance Organizer Model Learning by giving Structured Worksheets based on APOS Theory, (2) Improving student activity through the Advance Organizer Model Learning by giving Structured Worksheets based on APOS Theory. This research was a Classroom Action Research (CAR) which was carried out at SMK Negeri 1 Arse South Tapanuli. The research subject was grade 12 students of academy year 2012/2013 consisting 31 students, namely 18 males and 13 females. Object on this research were the student activity and student learning outcomes through the Advance Organizer Model Learning by giving Structured Worksheets based on APOS Theory. The research consisted of two cycles, each cycle consisting of three meetings. Test of achievement conducted at the end of each cycle. Test of achievement consisting of 15 questions. The results of the research are: (1) There is an increased of student learning outcomes on class XII Agribusiness Crop/Horticulture SMK Negeri 1 Arse which showed an increase in cognitive structure indicated strengthening of: (a) Outcomes of achievement test in the first cycle, namely: the average = 63.66; percentage of completeness = 41.94%, (b) Outcomes of achievement test in the second cycle, namely: the average = 82.58; percentage of completeness 90.32%. The percentage of completeness 48.39%, and the index gain 0.51 or moderate improvement criteria. (2) There is an increased of student activity on class XII Agribusiness Crop/Horticulture SMK Negeri 1 Arse shown from: first cycle is only the average of 59.72 up to 74.47 in the second cycle.